An update on the effect of intra-articular intervention strategies using nanomaterials in osteoarthritis: Possible clinical application - Amirsaadat, Soumayeh; Amirazad, Halimeh; Hashemihesar, Ramin; Zarghami, Nosratollah (Frontiers in Bioengineering and Biotechnology, 2023)
Osteoarthritis (OA) is the most common progressive condition affecting joints. It mainly affects the knees and hips as predominant weight-bearing joints. Knee OA (KOA) accounts for a large proportion of OA and presents numerous symptoms that impair quality of life, such as stiffness, pain, dysfunction, and even deformity. For more than two decades, intra-articular (IA) treatment options for managing KOA have included analgesics, hyaluronic acid (HA), corticosteroids, and some unproven alternative therapies. Before effective disease-modifying treatments for KOA, treatments are primarily symptomatic, mainly including IA corticosteroids and HA, so these agents represent the most frequently used class of drugs for managing KOA. But research suggests other factors, such as the placebo effect, have an essential role in the effectiveness of these drugs. Several novel IA therapies are currently in the clinical trial processes, such as biological therapies, gene and cell therapies, and small molecule – based therapies. Besides, it has been shown that the development of novel drug nanocarriers and delivery systems could improve the effectiveness of therapeutic agents in OA. This review discusses the various treatment methods and delivery systems for KOA and the new agents that have been introduced or are in development.